New Hope for the Expectations Hypothesis of the Term Structure of Interest Rates - FROOT, KENNETH A. (Journal of Finance, 1989)
ABSTRACT Survey data on interest rate expectations permit separate testing of the two alternative hypotheses in traditional term structure tests: that the expectations hypothesis fails, and that expected future interest rates are ex post inefficient forecasts. We find that the source of the spread's poor predictions of future interest rates varies with maturity. At short maturities the expectations hypothesis fails. At long maturities, however, changes in the yield curve reflect changes in expected future rates one‐for‐one, an implication of the expectations hypothesis. This result confirms earlier findings that long rates underreact to short rates, but now it cannot be attributed to term premia.